TINJAUAN PERKEMBANGAN PRESTASI SEPAKBOLA REMAJA DARI PENGALAMAN BERTANDING PADA PEMAIN KLUB ANGLING DARMA BOJONEGORO - OKTOBIONO, BANI (Jurnal Prestasi Olahraga, 2013)
The purpose of this research is to know the achievement of Angling Darma club based on the competition experience, especially on the club?s and player?s achievement, number of competitions that have been followed, number of exercises that have been followed and the coach?s point of view about young players of Angling Darma club. The function of this research is to give information about the achievement of Angling Darma Football club based on the competition experiences as the references to develop and improve the coaching of young football players to be the best. This research was conducted qualitatively. The data sources of this research were based on the data on Angling Darma club and the research method was descriptive. Methods in collecting the data were observation, interview and documentation. Result of the research shows that Angling Darma club during competition in 2011-2012 became the internal winner of Persibo Bojonegoro and one of the players got the top score. There was less number of competitions which was followed by the players, because the participants of Persibo Bojonegoro internal competition are only twelve clubs, but it can be solved by following another competition. Angling Darma football club has some schedules to exercise, those are Sunday, Tuesday and Thursday, but sometimes there is also on extra exercise and almost all players do their own exercise at home. Actually, using young players in a competition for Angling Darma club has several difficulties, because they are unstable since they often joke around when they do exercise, but the benefits are bigger than the difficulties. It is proved by Persibo Bojonegoro which became the winner of internal competition. Keywords: Young Players, Achievement, Competition Experiences, Exercise